2019
DOI: 10.1017/s1474747219000271
|View full text |Cite
|
Sign up to set email alerts
|

Annuity pricing in public pension plans: importance of interest rates

Abstract: This study examines the distribution options of 85 large public retirement plans covering general state employees, teachers, and local government employees. The interest rates used to price annuities vary considerably across the plans. As a result, retirees with the same monthly benefit if a single life benefit is chosen will have substantially different monthly benefits if they select a joint and survivor annuity. We examine the impact of variation in the pricing of annuity options using both cross-plan diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…By contrast, those authors reported that among public DC plans, an annuity was never the default distribution; moreover, some DC plans did not even offer an annuity option. Abashidze et al (2021) provide a review of the type of retirement plans offered by states and the benefit options included in these plans. 10…”
Section: Retirement Plan Distribution Optionsmentioning
confidence: 99%
“…By contrast, those authors reported that among public DC plans, an annuity was never the default distribution; moreover, some DC plans did not even offer an annuity option. Abashidze et al (2021) provide a review of the type of retirement plans offered by states and the benefit options included in these plans. 10…”
Section: Retirement Plan Distribution Optionsmentioning
confidence: 99%
“…By contrast, those authors reported that among public DC plans, an annuity was never the default distribution; moreover, some DC plans did not even offer an annuity option. Abashidze et al (2021) provide a review of the type of retirement plans offered by states and the benefit options included in these plans. 10 6 There are currently proposals in Congress to delay the RMD age to 75; see Waddell (2019).…”
Section: Retirement Plan Distribution Optionsmentioning
confidence: 99%